ANALISIS PENGARUH KEBIJAKAN KEUANGAN DAN TATA KELOLA TERHADAP NILAI PERUSAHAAN INDUSTRI MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE TAHUN - Sudirman abdi; maryam maryam (Fakultas Ekonomi Universitas Indonesia Timur, 2019)
ABSTRACT The development of Syariah Banking system in Indonesia in several years is fast enough, based on the data in the beginning of years 2015, which is profitably in 198,25 (Billion) IDR was increased to 258,10 Billion) IDR for September 2016, it is assumed to increased in 30,19 %. The profit was taken from three Syariah Banking system (202,76 (Billion) IDR with 78,56 % market share), while the comparative of Syariah banking system toward conventional banking system is 29,518 (Billion) IDR that has just reached 0,87 %. The market share is increased 0.07 % compared with September 2015 that is 0,80 %. There is anfluctuative increasing until 2016. This research aims at finding out : (1) the share holding is positively and significantly influencing toward the Mudarabah deposit, (2) the level of money interest is negatively and significantly toward the Mudarabah deposit. Data of this research is taken from the monthly report of PT. Bank Muamalat Indonesia and Indonesian Bank (BI). The data analyzed by using multiple regression method. This research is a case study at PT. Bank Muamalat Indonesia Tbk. The study population is the Financial statement and balance sheet of PT. Bank Muamalat Indonesia and data that is taken from Indonesian Bank (BI) about Mudarabah deposit, the level of share holding and the level of money interest during 2016-2018. Variables which are explored in this research includes the share holding, the level of money interest and Mudarabah deposit. Data was collected by using documentation. The result of this research has shown us that there is a positive and significant influence from the level of share holding and the level of money interest of Mudarabah deposit. The level of money interest has a negative and significant influence toward the Mudarabah deposit.